1985
DOI: 10.1007/bf00686997
|View full text |Cite
|
Sign up to set email alerts
|

Glial filaments are a major brain fraction in infantile neuronal ceroid-lipofuscinosis

Abstract: Extremely severe gliosis develops at the end stage of infantile neuronal ceroid-lipofuscinosis (INCL), a fatal encephalopathy characterized by accumulation of autofluorescent storage material in the brain and other tissues followed by a terminal subtotal neuronal and myelin loss. A major fraction of highly enriched intermediate filaments was obtained with a density gradient centrifugation method from INCL brain tissue, whereas the storage material represented only a minor fraction. SDS-polyacrylamide gel elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
4
14
0
1
Order By: Relevance
“…This well may have also occurred in the analysis of the Tibetian terrier model [22]. Indeed, it has been previously reported that GFAP constitutes a major fraction of the insoluble material in INCL brain autopsy specimens that initially cosediments with autofluorescent storage material but can be separated from this by further manipulations [40]. It is worth noting that vimentin, another intermediate filament protein, was also elevated in the storage body sample from the LINCL mouse, and this may represent the same phenomenon.…”
Section: Discussionmentioning
confidence: 86%
“…This well may have also occurred in the analysis of the Tibetian terrier model [22]. Indeed, it has been previously reported that GFAP constitutes a major fraction of the insoluble material in INCL brain autopsy specimens that initially cosediments with autofluorescent storage material but can be separated from this by further manipulations [40]. It is worth noting that vimentin, another intermediate filament protein, was also elevated in the storage body sample from the LINCL mouse, and this may represent the same phenomenon.…”
Section: Discussionmentioning
confidence: 86%
“…Highly elevated amounts of GFAP in INCL brain has been reported before [27], and may have caused the contamination of storage bodies with a small amount of this protein.…”
Section: Proteins In the Storage Materialsmentioning
confidence: 88%
“…In addition, quantities of ADAM12 mRNA were 18-fold higher in low grade tumors compared with high-grade tumors [70]. These authors also report that overexpression of ADAM12 did not co-localize with glial fibrillary acidic protein (GFAP), an intermediate filament protein expressed by various cell types of the central nervous system, and which is associated with CNS injury and formation of glial scars [71]. This selectivity suggests that ADAM12 may be a useful biomarker for identifying oligodendroglial cell subpopulations in mixed brain tumors [70].…”
Section: : Adam12mentioning
confidence: 99%